1994
DOI: 10.1095/biolreprod50.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst Cavitation is Accelerated by Ethanol- or Ionophore-Induced Elevation of Intracellular Calcium1

Abstract: To extend our previous finding that ethanol stimulates murine preimplantation development, we focused in the current study on the cavitation and expansion of the blastocyst. Ethanol stimulation of blastocyst cavitation and expansion was optimal at a concentration of 0.1% and required only a 5-min exposure. Because intracellular levels of calcium were transiently increased in the ethanol-exposed embryos, we determined the effect of directly increasing calcium on the rates of blastocyst cavitation and expansion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 54 publications
(72 reference statements)
4
40
0
Order By: Relevance
“…The post-fertilization calcium oscillations and the transients associated with nuclear envelope breakdown require factor(s) derived from the sperm that become associated with the nuclear membrane. There is no direct evidence of a developmental requirement for calcium transients in the mammalian early embryo outside these defined periods, although evidence that induction of artificial transients in morulae enhanced the rate of blastocyst formation (18,19) and the inhibition of embryo development by a calmodulin antagonist (W-7) suggests a role (20). It was recently shown (21) that exogenous PAF may induce calcium transients in the 2-cell mouse embryo although a mechanism for this action was not defined, nor was it established whether embryo-derived PAF also induced such responses.…”
mentioning
confidence: 99%
“…The post-fertilization calcium oscillations and the transients associated with nuclear envelope breakdown require factor(s) derived from the sperm that become associated with the nuclear membrane. There is no direct evidence of a developmental requirement for calcium transients in the mammalian early embryo outside these defined periods, although evidence that induction of artificial transients in morulae enhanced the rate of blastocyst formation (18,19) and the inhibition of embryo development by a calmodulin antagonist (W-7) suggests a role (20). It was recently shown (21) that exogenous PAF may induce calcium transients in the 2-cell mouse embryo although a mechanism for this action was not defined, nor was it established whether embryo-derived PAF also induced such responses.…”
mentioning
confidence: 99%
“…Su et al confirmed that TRPV5 was highly expressed in the mouse blastocyst by microarray analysis [13], and we also verified its strong expression in blastocysts, whereas the level was undetectable in ES cells (data not shown). Ca 2+ is an essential signal for many cellular processes in embryogenesis, e.g., fertilization [14], cavitation [15,16], blastocoel formation [15] and blastocyst outgrowth [17][18][19]. Taken together, BSPRY-1 may be involved in cell differentiation and division in the early embryo via regulation of Ca 2+ influx with TPRV5, and it may be one reason why the activity level of the two isoforms of BSPRY is different in early embryo and ES cells.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of ethanol to accelerate development at dissimilar stages from the one-cell to the blastocyst stage suggests that ethanol may affect key developmental regulatory mechanisms. It therefore appears that there is a threshold concentration of ethanol for increasing intracellular calcium [16].…”
Section: Introductionmentioning
confidence: 98%
“…Last studies have indicated that ethanol can activate oocytes and causes parthenogenesis [16]- [18]. Ethanol with changing signaling pathway, controls the rate of embryogenesis and can affect the development of preimplantation stage embryos [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation